A Project Management Case Study of PT QDC Trafo Bay Submission 150 kV at Lubuk Linggau, South Sumatera - Subekti, Rima Beladina; Yudoko, Gatot (Journal of Business and Management, 2015)
Abstract – PT. QDC Technologies is a company that works in the telecommunication and power infrastructure service sector in Indonesia. As an EPC (Engineering, Procurement, and Construction) company, it is important to have a well plan project managemnet to ensure that every project meets its project’s objectives. One of PT. QDC’s projects is the Trafo Bay Submission construction in Lubuk Linggau, South Sumatera, which project implementation run behind its project plan. This research is aimed to improve project management of PT. QDC to make a more effective and efficient project plan. Keywords – project managemnet, fishbone diagram, trafo bay construction project, case study